Probing single cell biomechanics with optical trapping and phonon microscopy - Hardiman, William (2024)
Single cell biomechanics is concerned with the viscoelastic properties of biological organisms on the length scales of whole cells and the macromolecules that comprise them (tens of microns to nanometres). This is an area of increasing research interest, with biomechanics being found to affect many healthy and diseased states of the cell. Many cell types are sensitive to the mechanical properties of their surroundings, which affects not only their own mechanical properties, but also such diverse things as mitotic cell division and stem cell differentiation. In probing cell mechanics, the cytoskeleton is of particular interest due to its multifaceted role; it is a prestressed network of proteinaceous filaments and cross-linkers which has been described as the source of order in the cell. The cytoskeleton is crucial to mechanosensing, force transduction, cell motility and division, and to regulation of the mechanical properties of cells. Many diseases are pathologies of the cytoskeleton, and it is a common target for anti-cancer drugs.